Integration of Islamic Religious Education Curriculum with the Independent Curriculum: A Framework for Holistic, Inclusive and Responsive Education - Dona Adi Bayu Saputra; Khoeron Khoeron (JIIS - Journal of Interdisciplinary Islamic Studies, 2026)
The integration of Islamic Religious Education (IRE) with the Independent Curriculum has emerged as a strategic approach to developing holistic, inclusive, and adaptive education in Indonesia. This study aims to analyze the concept of integrating the IRE curriculum with the Independent Curriculum, identify existing integration models, and formulate a framework that supports character development and religious moderation. A narrative literature review was employed by analyzing 25 relevant sources, including scientific journal articles, books, and official educational policy documents published between 2021 and 2026. Data were examined through thematic categorization, content analysis, and conceptual synthesis. The findings reveal that curriculum integration promotes contextual, collaborative, and student-centered learning while strengthening character education, critical thinking skills, tolerance, and religious moderation. The integrated curriculum also facilitates the development of cognitive, affective, and psychomotor competencies through holistic learning experiences. Furthermore, it contributes to creating inclusive and adaptive educational environments that respond effectively to contemporary social and educational challenges. The study concludes that integrating Islamic Religious Education with the Independent Curriculum provides a strategic framework for enhancing the quality and relevance of Islamic education in Indonesia. Future research should focus on examining the practical implementation and effectiveness of this integration in schools and madrasahs